2013
DOI: 10.1177/1090198113512127
|View full text |Cite
|
Sign up to set email alerts
|

Circles of Care

Abstract: Background Community-based peer support may help meet practical, emotional and spiritual needs of African Americans with advanced cancer. Support teams are a unique model of peer support for persons facing serious illness, but research is rare. This study sought to 1) implement new volunteer support teams for African Americans with advanced cancer in two distinct regions, and 2) evaluate support teams’ ability to improve support, awareness of services, and quality of life for these patients. Methods The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…53 A church-based volunteer peer support program has been found to provide support to African Americans with advanced cancer. 54 Even though QOL scores remained unchanged over the 2 months of the intervention, patients reported a decrease in their practical, emotional, and spiritual needs and a greater awareness of hospice services. 54 The National Hospice and Palliative Care Organization has developed an African American Outreach Guide with a strong focus in reaching out to spiritual and religious communities to increase the effectiveness of palliative care services for African American clients.…”
Section: Spiritual Religious and Existential Aspects Of Carementioning
confidence: 96%
See 2 more Smart Citations
“…53 A church-based volunteer peer support program has been found to provide support to African Americans with advanced cancer. 54 Even though QOL scores remained unchanged over the 2 months of the intervention, patients reported a decrease in their practical, emotional, and spiritual needs and a greater awareness of hospice services. 54 The National Hospice and Palliative Care Organization has developed an African American Outreach Guide with a strong focus in reaching out to spiritual and religious communities to increase the effectiveness of palliative care services for African American clients.…”
Section: Spiritual Religious and Existential Aspects Of Carementioning
confidence: 96%
“…54 Even though QOL scores remained unchanged over the 2 months of the intervention, patients reported a decrease in their practical, emotional, and spiritual needs and a greater awareness of hospice services. 54 The National Hospice and Palliative Care Organization has developed an African American Outreach Guide with a strong focus in reaching out to spiritual and religious communities to increase the effectiveness of palliative care services for African American clients. 6 Having a good understanding of a patient's spiritual belief system and practices is an essential component to providing high-quality palliative care, given the potential for drastically different beliefs related to illness, suffering, and death, which will inform how a patient approaches this transition.…”
Section: Spiritual Religious and Existential Aspects Of Carementioning
confidence: 96%
See 1 more Smart Citation
“…The support team model is an innovative form of community-based support adapted to the needs of seriously and chronically ill individuals. The basic model of a support team focuses on helping one person to meet a variety of needs and includes elements of peer support, focusing on the abilities of each team member (Hanson, Armstrong, et al, 2013; Hanson, Green, et al, 2013). Support team volunteers work together to provide practical, emotional, and spiritual support to a person who is open to receiving assistance (Buys, Marler, Robinson, Hamlin, & Locher, 2010; Hanson, Armstrong, et al, 2013; Hartman, Brooks, & Morrill, 2009).…”
mentioning
confidence: 99%
“…Volunteers offer to assist in a capacity they are comfortable with, in a coordinated way. Our research team has demonstrated the feasibility and acceptability of volunteer support teams for African Americans with cancer, called “Circles of Care” (Hanson, Armstrong, et al, 2013; Hanson, Green, et al, 2013). The support team model, developed in 1994 at the University of Alabama to improve care for patients with HIV, has only been described in two other peer-reviewed studies prior to its use in the current research: a support intervention for caregivers of persons with Alzheimer’s disease (AD; Stevens, Lancer, Smith, Allen, & McGhee, 2009) and a church-based home-delivered meals program (Buys et al, 2010).…”
mentioning
confidence: 99%